Evolution of magneto-orbital order upon B-site electron doping in Na1−xCaxMn7O12 quadruple perovskite manganites: Data archive - Johnson, R; Manuel, P; Khalyavin, D (University of Oxford, 2018)
Data presented in the graphical figures of our manuscript entitled ‘Evolution of magneto-orbital order upon B-site electron doping in Na1−xCaxMn7O12 quadruple perovskite manganites’ can be access here, in accordance with the EPSRC policy framework on research data. The data are provided in plain text files and in xye format. The file names identify the figure and the colour, symbol, and line of the data, as presented in the main manuscript. Full details of the data collection and analysis are provided in the main manuscript.